2012
DOI: 10.1037/a0028624
|View full text |Cite
|
Sign up to set email alerts
|

Working memory load reduces facilitated processing of threatening faces: An ERP study.

Abstract: The present study tested the hypothesis that facilitated processing of threatening faces depends on working memory load. Participants judged the gender of angry versus happy faces while event-related brain potentials were recorded. Working memory load was manipulated within subjects by the mental rehearsal of one- versus eight-digit numbers. Behavioral results showed that the relative slow-down to angry compared to happy faces in the gender-naming task (i.e., the negativity bias) was eliminated under high work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
57
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 62 publications
(91 reference statements)
12
57
2
Order By: Relevance
“…Furthermore, cognitive processes—such as working memory load or implicit emotion regulation—may have contributed to the absence of enhanced LPP to socially relevant angry faces. For instance, recent studies observed reduced LPP amplitudes to aversive stimuli under working memory load, suggesting that threat processing is contingent on available cognitive resources (MacNamara et al, 2011; Van Dillen and Derks, 2012). Alternatively, implicit emotion regulation may have reduced LPP amplitudes to aversive stimuli as shown in previous studies (Hajcak et al, 2010; Thiruchselvam et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cognitive processes—such as working memory load or implicit emotion regulation—may have contributed to the absence of enhanced LPP to socially relevant angry faces. For instance, recent studies observed reduced LPP amplitudes to aversive stimuli under working memory load, suggesting that threat processing is contingent on available cognitive resources (MacNamara et al, 2011; Van Dillen and Derks, 2012). Alternatively, implicit emotion regulation may have reduced LPP amplitudes to aversive stimuli as shown in previous studies (Hajcak et al, 2010; Thiruchselvam et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Emotional stimuli can influence cognition through beneficial or detrimental effects (e.g. enhanced processing of goal-relevant emotional stimuli or increased distraction due to goal-irrelevant emotional stimuli) (Dolcos and McCarthy, 2006; MacNamara et al , 2011; van Dillen and Derks, 2012; Luo et al , 2014; Uher et al , 2014). Previous studies that applied various cognitive tasks have suggested that the processing of task-relevant stimuli is impaired when emotional distracters are presented before (Pereira et al , 2006, 2010) or during the task (Vuilleumier and Schwartz, 2001; Erthal et al , 2005; Fernandes et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, interference should be reduced as task demands increase. There is support for this, i.e., that emotional interference effects are affected by cognitive load due to competition for attentional resources For example, research has shown that task-irrelevant emotional expressions interfere with performance on gender naming tasks during low but not high working memory load [3], [23]. These findings are supported by neuroimaging data showing decreased activity in emotion processing centres under conditions of increased load [10], [14], [24][26], although note that in the study by Erk et al [25], emotional distracters had no behavioural effect on task performance.…”
Section: Introductionmentioning
confidence: 99%
“…These include presenting emotional stimuli as background images (e.g., [19], [31]) or flanking stimuli (e.g., [18]) in an emotional n-back paradigm, or including emotionally expressive faces in a gender naming task [3], [23]. However, as the emotional aspect of these stimuli remains available for conscious processing and evaluation, responses may be influenced by metacognition, i.e., the ability to reflect on and regulate one's cognitive activity [32], [33].…”
Section: Introductionmentioning
confidence: 99%